2022
DOI: 10.1021/acsami.2c12850
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Controlled Conversion from CDS to MDS in an Azobenzene-Based Organic Memristor for Information Storage and Logic Operations

Abstract: For organic memristors, non-zero-crossing current−voltage (I− V) curves are often observed, which can be attributed to capacitive effects. If the conversion between the capacitance-dominated state (CDS) and the memristance-dominated state (MDS) can be realized in a controllable manner, more device functions can be obtained. In this work, a two-terminal memristor using a common organic dye, azobenzene (AZB), as the active layer was prepared. It is found that as the applied voltage gradually increases, the devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…With the research of memristors in information storage, neural synapses, neural networks, electronic skin (e-skin), and neuromorphic computing, it is suggested that memristors are a new type of electronic devices with great application prospects in overcoming the Von Neumann bottleneck and in the development of electronics in the post-Moore era. In particular, photoelectric memristor-based machine vision can be used in many fields, such as intelligent vehicles and real-time video analysis, requiring high resolution, high image capture speed, and detection capability under a range of lighting conditions. , Based on the above analysis of the research progress of photoelectric memristor-based machine vision, although many encouraging advances have been made in this field, the current research shows that there are also prominent problems, which can be summarized as follows . First, the current response and the corresponding current response range of the photoelectric memristor are very small after receiving the signal of light irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…With the research of memristors in information storage, neural synapses, neural networks, electronic skin (e-skin), and neuromorphic computing, it is suggested that memristors are a new type of electronic devices with great application prospects in overcoming the Von Neumann bottleneck and in the development of electronics in the post-Moore era. In particular, photoelectric memristor-based machine vision can be used in many fields, such as intelligent vehicles and real-time video analysis, requiring high resolution, high image capture speed, and detection capability under a range of lighting conditions. , Based on the above analysis of the research progress of photoelectric memristor-based machine vision, although many encouraging advances have been made in this field, the current research shows that there are also prominent problems, which can be summarized as follows . First, the current response and the corresponding current response range of the photoelectric memristor are very small after receiving the signal of light irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Williams et al established a reliable physical model and reported experimental results to confirm the theory pioneered by Chua . The two-terminal nonvolatile memory devices with resistive switching capability are considered as a memristor, which can maintain the internal resistance state according to the history of the applied voltage. , The resistance states of the memristor can be switched between the high-resistance state (HRS) and the low-resistance state (LRS) under applied voltage. Subsequently, logic operations based on memristors, artificial synapses, neural networks, and neuromorphic computing have been appeared one after another. Therefore, the research and application of memristors will have a revolutionary impact in the fields of information, semiconductors, and artificial intelligence.…”
Section: Introductionmentioning
confidence: 90%
“…It has a great deal of potential to enforce a large storage capacity, rapid data transfer rate, quick access time, facile manufacturing procedures, and nonvolatile nature, which can persuade the crucial necessities for forthcoming ultra-high-density data storage. 8,9 Recently, functionalized organic small molecules have received a lot of attention due to their potential benefits in resistive switching memory and have gained considerable attention as a strong contender for next-generation high-density data storage technology. 10,11 Their adaptability to tackle most practical difficulties of traditional Si-based memory systems created a high interest in researchers to explore them for future memory storage applications.…”
Section: ■ Introductionmentioning
confidence: 99%